Sedimentasi Pertemuan Dua Buah Sungai Pada Sungai Mangkauk dan Sungai Riam Kiwa - Holdani Kurdi (INFO-TEKNIK, 2007)
Naturally river’s  function as experienced basin to transport water from its stream area and conduct in gravitation to lower area. As water source which can be used for the irrigation of, agriculture, drinking water, industrial, energy generating, transportation. This research aim to give the analysis form and place of where there are sediment load which is there in the meeting of Riam Kiwa River and Mangkauk River which is resulted by the existence of wide difference of dimension of the river and stream speed. Method used to calculate basic speed, sediment with Van Rijn method, because entangling factor speed of the river flow and basic sediment concentration.From solution result got the following conclusion: stream speed, wide and form the river very influencing to the number of sediment which can be lifted and precipitated by current, sediment item which have diameter to smaller than 2,0 mm earn is easily brought by river stream, and form the river meeting very influencing of pattern of sediment that happened. Therefore the importance of furthermore research about sediment in the river, particularly at two river cross)